(untitled) (Journal of Current and Advance Medical Research, 2018)
Background: Type 2 diabetes mellitus is a chronic disease characterized by relative or absolute deficiency of insulin, resulting in glucose intolerance. Objectives: The present study was planned to see the associations of serum uric acid with positive Rheumatoid factor in type 2 male diabetes mellitus patients. Methodology: This case control study was carried out at the department of Biochemistry at Ibrahim Medical College, Dhaka, Bangladesh. The duration of the study was from June 2015 to June 2016 for a period of one year. In this present study, male patients with type 2 diabetes mellitus were taken as case group and age and sex matched healthy male were taken as control group. Rheumatoid factor was measured from the blood of all case and control group respondents. Others blood para meters were also measured for the correlation with the diabetes mellitus patients. Results: In this present study, 110 male patients presented with type 2 diabetes mellitus were recruited as case and age and sex matched healthy male were recruited as control. More rheumatoid factor positive in type 2 DM male patients with the uric acid range between 6.5 to 9.5 mg/dL. The number of patients was 5 out of total 9 rheumatoid factor positive cases. In this study serum uric acid was significantly correlated with rheumatoid factor in type 2 male diabetic patients. Rheumatoid factor positive cases were taking insulin among 9 and it was statistically significantly associated (p<0.001). Conclusion: In this study serum uric acid is significantly associated with positive rheumatoid factor in type 2 male diabetic patients. Journal of Current and Advance Medical Research 2017;4(2):58-62